PRAKTEK PROSTITUSI TERSELUBUNG DI KOTA BIMA - Adnan Adnan; Juhriati Juhriati; Syamsuddin Syamsuddin (Fakultas Syariah IAI Muhammadiyah Bima, 2017)
This paper is summary of the result of research conducted in Kota Bima. It was tried to open the prostitution mask which is done by the students. Besides, the research is a way to search the prostitution motive and how to solve it. The type of this research is the empiric and sociological law, meanwhile, the data is collected by field observation and directly interview. The data of research was analyzed by description method, to describe the data, it need more explanation to solve the prostitution. The result of this research show, there are two main factors why the students do prostitution; firstly internal factor which are consist of low of moral standardization and low of iman quality ( Believe to God), life style, psychological burden (traumatic and disappointed). While the external factor is influence by environment (friends), lack of parents, social, or government watching. However, the dominant factor is demand of students life – style who wants life luxury and expensive. Finally, the students can do the prostitution because lack of parent, social (owner the building house, hotel or homestay) and government roles.